InSAR investigation of sackung-like features and debris flows in the vicinity of Hawkesbury Island and Hartley Bay, British Columbia, Canada - Huntley, D.; Rotheram, D.; Bobrowsky, P.; Lintern, G.; MacLeod, R.; Brillon, C. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Future development in coastal northwest British Columbia requires safe, secure locations for infrastructure installations and communities. The challenge for managing environmental and infrastructure protection and site reclamation will be to accommodate future extreme weather events, climate change, and damage from earthquakes, landslides and tsunamis. New insights into the terrestrial and marine geohazards offered by our work will help reduce the future development risks to governments, resource industries, communities and the environment. SAR imagery captures two debris flow events in the vicinity of Hartley Bay that occurred between September 2017 and January 2018 during fall or winter storm events. SAR imagery also captures flooding in a nearby lake basin over this period. The extent to which the debris flows detected impacted local watersheds has yet to be determined by ground observations and public consultation. For Hawkesbury Island and the surrounding area, a provisional InSAR analysis suggests that on short time-scales (< 2 years), the deep-seated, sackung-like bedrock fractures observed on the western flank are stable. These paraglacial features were likely formed by stress release during debuttressing of side walls, glacio-isostatic rebound, neo-tectonic faulting, and permafrost loss during deglaciation. This finding has implications for landslide and tsunami risk assessments, suggesting the stable western flank of Hawkesbury Island does not represent a geological hazard to fjord-bound communities, coastal infrastructure, and natural resource activities.